Global Research Hotspots and Progress on Acrylamide: Visualization Analysis - Shaher Zyoud; Sa’ed H. Zyoud (Environmental Health Insights)
Acrylamide is a contaminant prevalent in many commonly consumed foods, contributing to unavoidable human exposure. It is recognized as likely to be carcinogenic to humans as well, provoking global concerns. Numerous studies have investigated the impacts of acrylamide formation on food and drink, nutrition, and health. The intent of this analysis is to quantify global acrylamide research, evaluate recent developments, and recognize emerging trends, along with assessing research dynamics as an indicator of innovation among the scientific community. The Scopus database was used to perform an in-depth investigation of scientific publications on acrylamide from 1949 to 2023. Exploring prominent topics and the knowledge network related to the topic was conducted via VOSviewer version 1.6.20. Additionally, using SciMAT software, intellectual analysis was conducted to identify both driving and emerging themes in acrylamide-related research. A total of 11 880 publications on acrylamide were identified, with 10 720 (90.24%) being original articles. The leading contributors in terms of publication output were China (n = 2452; 20.64%), followed by the USA (n = 1564; 13.16%), and India (n = 952; 8.01%). The predominant themes were associated with (a) the functionalization of acrylamide polymers and (b) the formation and mitigation of acrylamide in food and drinks. Driving themes that will continue to shape the future of acrylamide research involve unraveling the synthesis of acrylamide; deploying acrylamide in nanocomposites to increase contaminant removal; investigating the genotoxicity of acrylamide, as well as its carcinogenic, reproductive, and neurotoxic effects; and researching the adsorption characteristics of acrylamide in aqueous solutions. In particular, an increased focus has been placed on understanding the formation and mitigation of acrylamide in recent years, signifying increased attention and alignment with the latest scientific advancements in this field. The creation of research plans in this way is significant, particularly in shaping future health policies.